BALANCE SCORECARD: MODEL, IMPLEMENTASI, DAN DAMPAK TERHADAP KINERJA INSTITUSI PENDIDIKAN - Nabila Qathrunnada; Qomariya Rahma Ayu; Ali Mustofa; Hanun Asrohah (STKIP Pesisir Selatan, 2026)
This study aims to conduct an in-depth analysis of the conceptual model of the Balanced Scorecard (BSC), its implementation in various educational institutions, and its impact on institutional performance. The study seeks to assess the extent to which the BSC can serve as a strategic instrument that aligns an institution’s vision, mission, and strategy with measurable and balanced performance indicators across academic, administrative, and spiritual dimensions. This research employs a Systematic Literature Review (SLR) as the primary approach to review and synthesize previous studies related to the model, implementation, and impact of the Balanced Scorecard (BSC) in educational institutions. The findings indicate that the application of the BSC significantly enhances the effectiveness, efficiency, and accountability of educational organizations. The four main perspectives of the BSC—financial, customer, internal process, and learning and growth—are proven to strengthen institutional governance and stakeholder satisfaction. Most prior studies employed descriptive or single-case study approaches, resulting in limited cross-institutional and cross-national synthesis. Therefore, this study fills that gap by conducting an SLR on numerous open-access articles, providing a more comprehensive synthesis and reinforcing the empirical evidence on the effectiveness of the Balanced Scorecard in education.